Harnessing Information Systems for Climate Action: A Librarian's Perspective - Maina, John; Muthii, Selina; Musungu, Mercy; Kibos, Jane; Mwiti, Faith (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
In the contemporary era, librarians play a pivotal role in addressing the global challenge of climate change by leveraging information systems to enhance climate action initiatives. This study explores the intersection of library science and climate science through the lens of a systematic review. The ideal situation hypothesizes librarians as proactive agents utilizing information systems to bridge the gap in climate knowledge management. The identified problem lies in the underutilization of librarians' potential in climate action, creating a gap in efficient information systems for climate research. The objective of this systematic review is to assess existing literature, methodologies, and initiatives where librarians actively contribute to climate action. The methodology employed involves a comprehensive systematic review of peer-reviewed articles, reports, and case studies, ensuring a thorough exploration of the librarian's role in climate-related information management. The research design follows established systematic review protocols, ensuring the validity and reliability of the findings. Quality assessment criteria are applied to selected studies to uphold the consistency of the review process. Key findings reveal that librarians significantly contribute to climate knowledge management through information systems, enhancing the accessibility and dissemination of critical climate data. The brief discussion emphasizes the importance of integrating librarians into interdisciplinary collaborations addressing climate change. The application of these findings lies in informing institutions, policymakers, and library professionals about the potential impact of librarians in climate action. Conclusively, the systematic review underscores the need for recognizing and empowering librarians in the broader discourse on climate resilience. Recommendations include the integration of climate literacy into library science education, fostering collaboration between librarians and climate scientists, and developing information system frameworks tailored to climate research needs. This research contributes to the ongoing dialogue on the vital role of librarians in achieving sustainable climate action.